Associated Factors for Antegrade Continence Enemas for Refractory Constipation and Fecal Incontinence. Issue 4 (October 2016) - Gomez-Suarez, Roberto A.; Gomez-Mendez, Michelle; Petty, John K.; Fortunato, John E.
ABSTRACT: Objective: Determine clinical and manometric parameters associated with success of antegrade continence enemas (ACEs) administered via cecostomy in the treatment of constipation and fecal overflow incontinence. Methods: We performed a retrospective review of clinical symptoms and manometry (colonic and anorectal) before cecostomy in 40 pediatric patients (20 males, 20 females). The mean age at time of follow-up was 9.5 ± 4.4 years with a mean follow-up time of 12.2 ± 10.9 months. Clinical outcomes were defined as good, if subjects had >3 bowel movements per week, <2 episodes of soiling per week, and absence of pain at the time of follow-up after cecostomy. Results: Before cecostomy, the mean duration of constipation and/or fecal incontinence was 7.7 ± 4.4 years, mean number of BMs was 1.5 ± 0.9 per week, and soiling episodes 4.12 ± 3.5 per week; 24 (60%) patients had abdominal pain. At follow-up 30 out of 40 patients had a good outcome, and 10 had a poor outcome; with a difference in the number of weekly BM of 5.7 ± 2.2 versus 1.5 ± 0.9, P < 0.001, and soiling episodes (0.4 ± 1.5 vs 4 ± 3.1, P < 0.001). There was no difference in the duration of symptoms between groups. Obesity was more common in the poor-outcome group, 60% versus 21% ( P = 0.01). Abdominal pain was more common in the poor-outcome group, 100% versus 47% ( P = 0.003). Normal colonic manometry was associated with good outcome, whereas absence of high-amplitude propagating contraction (HAPC) in any part of the colon was associated with poor outcome. No other differences in colonic manometry were observed between the good- and poor-outcome groups with the exception of a trend toward decreased number of sigmoid HAPCs in the poor-outcome group ( P = 0.07). No differences were observed in anorectal manometry measurements between good- and poor-outcome groups with the exception of an observable increased baseline resting pressure in the poor outcome ( P = 0.05). Conclusions: Obesity and abdominal pain tend to be associated with poor outcomes after cecostomy for refractory constipation. Normal colonic and anorectal manometry were associated with good outcome. Absence of HAPC in any part of the colon, and increased baseline resting pressure of the anal canal were more associated with poor outcome. No other specific differences in either colonic or anorectal manometric parameters were observed in patients with good versus poor outcomes with cecostomy. Large prospective studies potentially combining other diagnostic modalities such as colonic transit studies are needed to determine the optimal tests to predict successful outcomes from cecostomy.